Use of helium-neon laser in patients with melasma - Ana Lucía Jacas Portuondo; Natacha López Pupo; Yaimaris Girón Maturell; Nancy Téllez Céspedes (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Melasma is a hyperpigmentation of the skin located in photo-exposed areas, which is caused by an increase in epidermal or dermal melanin, or both, which sometimes affects the self-esteem of men and women. Objective: To assess the effectiveness of helium-neon laser treatment in patients with melasma. Methods: A quasi-experimental study of therapeutic intervention was carried out in 34 patients with a clinical and dermoscopic diagnosis of melasma, treated at the dermatology clinic of the Dr. Juan Bruno Zayas General Teaching Hospital in Santiago de Cuba, from January 2019 to the same month of January 2019. 2020, for which two groups were formed: I (or intervention), which received laser treatment, and II (control), treated with 2% hydroquinone cream. The information was processed and expressed in absolute values and percentage; likewise, if necessary, the Χ2 parametric homogeneity test was used to search for association between the groups, with a significance level of α=0.05. Results: Most of the patients were between the ages of 39-48 years old, female, with mixed skin color and medium-sized lesions with evaluations at the beginning, at the end of treatment, one month and 3 months after finishing it. Results: The use of helium-neon laser was effective in the patients, with no statistically significant differences in terms of therapeutic response between both groups and no adverse events.